ESTIMATING FINANCIAL SUPPORT OF REGIONAL PROGRAMS OF SOCIAL ECONOMIC DEVELOPMENT - Kokhan, I. V. (The actual problems of regional economy development, 2016)
The given article presents the analysis of the experience of the financial support of the regional programs of social economic development and the areas of usage of internal and external resources of the area. Dynamic and balanced development of regions is one of the most important issues for further establishment of marketing relations and social transformations in Ukraine. The Aim lies in the evaluation of financial support of the approved regional programs and launching the amount of their financing. The assessment of social economic situation in Ivano-Frankivsk region in terms of nationwide tendencies allows asserting that economic growth depends on the amounts and sources provided by the state. To determine close connection between the amount of financing for the programs and gross domestic product, the coefficient of correlation was calculated according to Pierson. It was proved that the amount of financing regional programs of social economic development influences the growth rate of gross domestic product. During research period the activation of regional authority institutions is being surveyed regarding the adoption and financing target regional programs. It was determined that the dynamic activity of the regional community and its territorial units on realization in terms of defined strategic priorities for programs of social economic development will facilitate disproportion reduction and differences in the development of territory units in the region, as well as positively influences the growth of gross domestic product providing steady increase of social welfare. JEL: R 58